Attenuated SIRT1 Activity Leads to PER2 Cytoplasmic Localization and Dampens the Amplitude of Bmal1 Promoter-Driven Circadian Oscillation - Ashimori, Atsushige; Nakahata, Yasukazu; Sato, Toshiya; Fukamizu, Yuichiro; Matsui, Takaaki; Yoshitane, Hikari; Fukada, Yoshitaka; Shinohara, Kazuyuki; Bessho, Yasumasa (Frontiers in Neuroscience, 2021)
The circadian clock possesses robust systems to maintain the rhythm with approximately 24 hours, from the cellular to organismal levels, whereas aging is known to be one of the risk factors linked to the alternation of circadian physiology and behavior. The amount of many metabolites in the cells/body alter with the aging process, the most prominent metabolite among them is NAD+, which is associated with post-translational modifications of acetylation and poly ADP-ribosylation status of circadian clock proteins, and decreases with aging. However, how low NAD+ condition in cells, which mimics aged or pathophysiological conditions, affects circadian clock is largely unknown. Here, we show that low NAD+ in cultured cells promotes PER2 to be retained in the cytoplasm through NAD+/SIRT1 axis, which leads to the attenuated amplitude of Bmal1 promoter-driven luciferase oscillation. We found that among the core clock proteins PER2 is mainly affected in its subcellular localization by NAD+ amount, higher cytoplasmic PER2 localization was observed under low NAD+ condition. We further found that NAD+-dependent deacetylase SIRT1 is the regulator of PER2 subcellular localization. Thus, we anticipate that the altered PER2 subcellular localization by low NAD+ is one of the complex changes that occurs in the aged circadian clock.